Problem-Based Learning to improve the speaking skill in EFL - Núñez Moreira, Wendy Elizabeth (2021)
The following research aims to determine the improvements that can be obtained thanks to the application of the PBL (Problem-Based Learning) methodology, in addition to identifying the impact it generates on speech skills in students at level A1 of the English proficiency program belonging to the Technical University of Cotopaxi Extension "La Maná" where different difficulties have constantly been presented in the language teaching-learning process. One of the most notorious problems during English classes is the low participation in classes, in addition to the lack of interest and fear that students present, so the implementation of the PBL Methodology is sought, accompanied by tools such as surveys to determine the effectiveness of itself. After applying a pre-test online and after having analyzed the results, an understanding is reached of a significant incidence both in errors that occur in the grammatical structure, such as the lack of a basic and necessary vocabulary for the assigned level and also the level necessary to improve pronunciation. This research has a quantitative-qualitative, quasi-experimental, descriptive and explanatory approach with deductive, synthetic and analytic methods. The teacher has the responsibility of applying an appropriate methodology for the group of students, otherwise the teaching-learning process will not be carried out correctly, based on this premise, the proposal of a brochure with 5 units is presented where the methodology of PBL (Learning Based in Problems) and later, after having obtained results, they will be compared with the results previously acquired through the Pre-test. If an improvement in their speech skills is determined, thus improving the problems raised, it can be assumed that students will be able to cope in different situations of daily and professional life with a meaningful learning and a large vocabulary.